Anisotropic phase stiffness in infinite-layer nickelates superconductors - Xu, Minyi; Qiu, Dong; Xu, Minghui; Guo, Yehao; Shen, Cheng; Yang, Chao; Sun, Wenjie; Nie, Yuefeng; Li, Zi-Xiang; Xiang, Tao; Qiao, Liang; Xiong, Jie; et al. (Nature communications, 2025)
In unconventional superconductors such as cuprates and iron pnictides and chalcogenides, phase stiffness—a measure of the energy cost associated with superconducting phase variations—governs the formation of superconductivity. Here we demonstrate a vector current technique enabling in-situ angle-resolved transport measurements to reveal anisotropic phase stiffness in infinite-layer nickelate superconductors. Pronounced anisotropy of in-plane resistance manifests itself in both normal and superconducting transition states, indicating crystal symmetry breaking. Remarkably, the electric conductivity of Nd 0.8 Sr 0.2 NiO 2 peaks at 125° between the direction of the current and crystal principal axis, but this angle evolves to 160° near zero-resistance temperature. Further measurements reveal that the phase stiffness maximizes along 160°, a direction distinct from the symmetry axis imposed by both electronic nematicity and the crystal lattice. Identical measurements conducted on a prototypical cuprate superconductor yield consistent results. By identifying the contrasting anisotropy between electron fluid and superfluid in both nickelates and cuprates, our findings provide clues for a unified framework for understanding unconventional superconductors. The authors study nickelate superconductor Nd0.8Sr0.2NiO2 by angle-dependent transport. They find that the superconducting phase stiffness is anisotropic, and that electrical conductivity peaks along the direction with maximized phase stiffness.